2017
DOI: 10.3928/24748307-20171005-01
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Competencies for European Health Care Personnel

Abstract: Background: Health literacy as a concept is gaining importance in European countries, although it is still not adequately addressed among health personnel. Health literacy supports the self-management of patients in maintaining and improving health, which could decrease the burden on health systems in Europe. However, health professionals lack adequate knowledge about health literacy and the skills to promote health literacy among their patients. Objective: The Health L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 43 publications
2
26
0
3
Order By: Relevance
“…Being able to identify people with limited HL will help GPs to tackle health inequalities, for example by adequate information exchange. Hence, GPs should be equipped with a variety of strategies they can integrate in their day-to-day practice to communicate on a low HL level 55–57…”
Section: Discussionmentioning
confidence: 99%
“…Being able to identify people with limited HL will help GPs to tackle health inequalities, for example by adequate information exchange. Hence, GPs should be equipped with a variety of strategies they can integrate in their day-to-day practice to communicate on a low HL level 55–57…”
Section: Discussionmentioning
confidence: 99%
“…Participants' confidence in both their own and their organisation's ability to be responsive to health literacy improved from baseline following participation in the Org-HLR Tool and Assessment Process. Consistent with studies of health professionals in the USA and Europe [29][30][31][32], participants' initial understanding of health literacy was limited to the communication of health information to individuals in a way that patients could understand. Participants described how their understanding of health literacy expanded as a result of the workshops to be a much broader concept affecting the entire community, not just individuals, in line with recent definitions of health literacy [27].…”
Section: Evaluation Of the Org-hlr Tool And Assessment Processmentioning
confidence: 67%
“…Studies have consistently found that healthcare professionals in the USA and Europe have a limited understanding of health literacy and often lack the skills required to respond to the health literacy needs and preferences of the population [29][30][31][32]. Despite this, only a small number of professional development tools and guidelines targeting organisational health literacy responsiveness have been developed [30]. The US Institute of Medicine's (IOM) Ten Attributes of Health Literate Health Care Organisations are the most widely used internationally; however, this is not an exhaustive list and requires further development [27].…”
Section: Organisational Health Literacy Responsivenessmentioning
confidence: 99%
“…The HLQ survey is being culturally adapted and validated within European countries [13,14], enabling comparison of the health literacy of health profession students across continents. This will provide opportunities for international collaboration in the development of health literacy resources [21,28]. Additionally, longitudinal studies will provide valuable information regarding the health literacy of beginning practitioners within various health disciplines, and the impact on health literacy levels of healthcare recipients over time.…”
Section: Future Directionsmentioning
confidence: 99%